Memory in the digital age [version 1; peer review: 1 approved, 2 approved with reservations] - Silvana Mandolessi (Open Research Europe, 2023)
This article explores the configuration of collective memory under the impact of the digital turn. In recent debates, there has been a marked tendency to interpret ‘digital memory’ as a new type of memory, which is radically different from the traditional conceptualization. Even leading authors in the field claim that the digital revolution implies the end of collective memory. However, I argue that despite the transformations that memory undergoes in the digital age, these changes do not imply a new ontology of memory but rather a materialization of the theoretical claims made by Memory Studies since the field's inception. To support this hypothesis, I analyze digital memory in relation to three topics: first, I focus on the problematic definition of collective memory to demonstrate how the digital realm allows us to rethink the social nature of memory through a different concept of the social. By contrasting Halbwachs' notion of the social, which forms the basis of memory studies, with the alternative proposal of Gabriel Tarde, I argue that the latter enables us to refine the concept of the ‘collective’ that we have inherited from the founding figure of memory studies. Second, I delve into the new ontology of the digital archive showing how it materializes one of the defining features of collective memory: its mobile, dynamic, and procedural nature. Lastly, I address the inversion of the dialectic between memory and forgetting to highlight the specificity of these practices in the digital environment. I demonstrate how these changes effectively implement, surpassing older technologies, the concept of collective memory as a distributed and dynamic technological process that shapes our shared representations of the past.